If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7.5(-0.9w + -9) + -6 = 0 Reorder the terms: 7.5(-9 + -0.9w) + -6 = 0 (-9 * 7.5 + -0.9w * 7.5) + -6 = 0 (-67.5 + -6.75w) + -6 = 0 Reorder the terms: -67.5 + -6 + -6.75w = 0 Combine like terms: -67.5 + -6 = -73.5 -73.5 + -6.75w = 0 Solving -73.5 + -6.75w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '73.5' to each side of the equation. -73.5 + 73.5 + -6.75w = 0 + 73.5 Combine like terms: -73.5 + 73.5 = 0.0 0.0 + -6.75w = 0 + 73.5 -6.75w = 0 + 73.5 Combine like terms: 0 + 73.5 = 73.5 -6.75w = 73.5 Divide each side by '-6.75'. w = -10.88888889 Simplifying w = -10.88888889
| x^2+2=3y | | 3x^3+5x-24=0 | | 4x+8x=2(6x-12) | | 4(8-5x)=25 | | -8+22=15x-2-14x | | (8a-5x)2= | | x-6=-2-24 | | -47.62=k+89.2 | | 2x^2+22x+54=0 | | (7+3y)2= | | 6x=3(2x+5) | | 180k^2+300k+125=0 | | 6m-(31m-18)=12(m-1)+3m | | y=8-(1/2)x | | 160x^2-250=0 | | -3c^2+4c-4= | | h=25433(9.5)+28.465 | | 6x+8-4x=20 | | 4(k-2)-6=3k-(2k-3) | | m+m+18=31 | | 243g^2+54g+3=0 | | 61*ln(y)=13 | | 4/3p=9/8 | | 5(2x-6)=25 | | 2(p+9)= | | 4x-3y+z=4 | | 4x+3(2-3x)=40 | | 3x=5+2(3+1x) | | 3(x+3)-3=7(x+1)-4x | | x^3+2x^2+x= | | (x-1)(-6x+6)= | | 7x-5(x+1)+9=19 |